Immediate loading over lower prosthesis in edentulous mandibles: comparison between two types of prosthetic connection - Oliveira, Marina Reis (2017)
ABSTRACTObjective: This study evaluated two implant-abutment connection systems under immediate loading of lower prosthesis in edentulous mandibles.Methods: Seventy-two implants placed in 18 patients were analyzed. The parameters evaluated included probing depth, stability of implants and perimplant bone loss, which were measured immediately when installing the prosthesis and after 3 and 6 months. All data underwent statistical analysis (T-Test and ANOVA, 5% significance level).Results: Implants with Morse cone connections showed smaller, statistically significant probing depth values for all periods (0.68/1.19/1.31), when compared to the external hexagon connections (1.08/1.52/1.64). A statistically significant difference was observed between baseline, 3 months (p<0.01 for Morse cone; p<0.001 for external hexagon) and 6 months (p<0.001 for both connections). When periods were considered there was a statistically significant difference in Implant Stability Quotient ISQ values between baseline and 6 months for both prosthetic connections.Conclusion: Immediate loading of the lower prosthesis is a viable option for the treatment of edentulous mandibles and that the external hexagon or Morse cone connections do not interfere with the success of the implants in a short-term evaluation.